A Study on Awareness, Attitude and Myths Regarding Swine Flu Pandemic in Rural Communities of Coastal Karnataka: A Cross- Sectional Study - E., Vinu; Kini, Sanjay; Badiger, Sanjeev; Kiran, N. Udaya (Journal of Health and Allied Sciences NU, 2017)
Introduction: Swine flu being a dreadful disease, without an ounce of doubt, has caused a major fear among the common people of India across various strata of the society. In global terms, India was one of the most affected countries in terms of magnitude of cases and deaths of swine flu (influenza A H1N1) during the 2009 influenza pandemic which caused a lot of public hype and panic.Objectives: To study the awareness, attitude and myths regarding swine flu pandemic in a rural community of coastal KarnatakaMethodology: A cross sectional study was conducted in rural field practice area of the department of community medicine of K.S Hegde Medical Academy during the year 2015, using a pre-tested semi-structured questionnaire, consisting of details on socio-demographic factors, awareness and attitude about swine flu.Results: A total of 365 subjects were interviewed using a pretested semi-structured questionnaire. 67.3 % of the subjects were aware about swine flu, tele-media being the major source of information. Among those who were aware about swine flu, 35.3% of subjects knew about the preventive measures.Conclusion: There is a need to build strategies to create more awareness about swine flu pandemic through effective mass media which is vital for containing the pandemic.
Keywords: Awareness; Swine flu; Coastal Karnataka